The Stability of Social Desirability: A Latent Change Analysis. Issue 4 (19th August 2014) - Haberecht, Katja; Schnuerer, Inga; Gaertner, Beate; John, Ulrich; Freyer‐Adam, Jennis
Abstract Social desirability has been shown to be stable in samples with higher school education. However, little is known about the stability of social desirability in more heterogeneous samples differing in school education. This study aimed to investigate the stability of social desirability and which factors predict interindividual differences in intraindividual change. As part of a randomized controlled trial, 1, 243 job seekers with unhealthy alcohol use were systematically recruited at three job agencies. A total of 1, 094 individuals (87.8%) participated in at least one of two follow‐ups (6 and 15 months after baseline) and constitute this study's sample. The Social Desirability Scale‐17 was applied. Two latent change models were conducted: Model 1 tested for interindividual differences in intraindividual change of social desirability between both follow‐ups; Model 2 included possible predictors (age, sex, education, current employment status) of interindividual differences in intraindividual change. Model 1 revealed a significant decrease of social desirability over time. Model 2 revealed school education to be the only significant predictor of change. These findings indicate that stability of social desirability may depend on school education. It may not be as stable in individuals with higher school education as in individuals with lower education.